Digital Feminism and the Rise of Online Activism in Social Media Movements - Gede, Ketut; Dewa, Artha; Luh, Ni (Journal Social Humanity Perspective, 2025)
This paper will discuss the digital feminism phenomenon and emergence of online activism in social media movements in relation to how feminist players take advantage of social media channels by incorporating digital media to instigate changes in gender inequalities, mobilize masses and cause social change. Social media in the modern age has revolutionized the field of activism through granting visibility, intersectional interaction and hybrid modes of participation which connect online and offline action. Using a qualitative research design, this project uses digital texts, social media content and interviews of feminist activists to examine the strategies, narratives, and issues of digital feminist practices. The results show that digital platforms empower decentralized and participatory activism which enables voices of the marginalized to be heard and it creates the possibility of collective identity formation. Meanwhile, activists constantly deal with considerable amounts of emotional work, harassment on the internet, and the limitations of the platform, which requires adaptation and context-driven approaches. Besides, the paper shows that digital feminism is highly intersectional and place-based by representing cultural, political, and technological conditions, but also engaging in the global feminist discourse. Significantly, the study draws your attention to the fact that modern-day activism is a hybrid, meaning that online mobilization often manifests itself in offline action, such as lessons, advocacy work, and community organizing. The findings promote theoretical knowledge of feminism in the digital era, as well as provide practical suggestions on how to maintain the resilient, inclusive, and ethically informed feminist movements. This paper places digital feminism into the broader social, cultural and organizational contexts to emphasize how it can transform and bring social justice to more digitalized societies and bring about equitable change.